Healthcare Cost Differences with Participation in a Community-Based Group Physical Activity Benefit for Medicare Managed Care Health Plan Members - Ackermann, Ronald T. (2008)
OBJECTIVES: To determine whether participation in a physical activity benefit by Medicare managed care enrollees is associated with lower healthcare utilization and costs. DESIGN: Retrospective cohort study. SETTING: Medicare managed care. PARTICIPANTS: A cohort of 1,188 older adult health maintenance organization enrollees who participated at least once in the EnhanceFitness (EF) physical activity benefit and a matched group of enrollees who never used the program. MEASUREMENTS: Healthcare costs and utilization were estimated. Ordinary least squares regression was used, adjusting for demographics, comorbidity, indicators of preventive service use, and baseline utilization or cost. Robustness of findings was tested in sensitivity analyses involving continuous propensity score adjustment and generalized linear models with nonconstant variance assumptions. RESULTS: EF participants had similar total healthcare costs during Year 1 of the program, but during Year 2, adjusted total costs were $1,186 lower (P=.005) than for non-EF users. Differences were partially attributable to lower inpatient costs (−$3,384; P=.02), which did not result from high-cost outliers. Enrollees who attended EF an average of one visit or more per week had lower adjusted total healthcare costs in Year 1 (−$1,929; P<.001) and Year 2 (−$1,784; P<.001) than nonusers. CONCLUSION: Health plan coverage of a preventive physical activity benefit for seniors is a promising strategy to avoid significant healthcare costs in the short term.